ERYTHROCYTE OMEGA-3-POLYUNSATURATED FATTY ACIDS, SELECTED ANTIOXIDANTS AND CARDIOVASCULAR DISEASE RISK FACTORS IN ELDERLY NIGERIANS WITH DEMENTIA (2012)
Dyslipidemia, reduced omega-3 and -6 fatty acids and vitamins are risk factors for cerebrovascular disease associated with dementia. Prognosis differs between Alzheimer’s disease (AD) and Vascular Dementia (VD) but derangements of the fatty acids and their clinical values for making distinction are unclear. In addition, inadequate antioxidant levels have been associated with hyperhomocystenemia in dementia patients. Therefore, levels of lipids, omega-3 and-6 fatty acids, folate, homocysteine, selenium and vitamin E were evaluated in VD and AD patients. Forty consenting patients with VD and fifteen with AD were recruited at the University College Hospital, Ibadan. Forty healthy adults served as control group. Anthropometric indices and Blood Pressure (BP) were measured in all subjects. Fasting venous blood sample was obtained and erythrocytes were separated by centrifugation. High Performance Liquid Chromatography (HPLC) was used for analysis of erythrocyte fatty acids: Docosahexanoic Acid (DHA), Eicosapentanoic Acid (EPA), Linolenic Acid (LA) and Arachidonic Acid (AA) as Total Fatty Acids (TFA). Plasma homocysteine was determined using HPLC with fluorescence detection. Plasma folate was determined by Ion Capture Technology using pteroic acid and alkaline phosphatase as signal-generators; vitamin-E by colorimetry; selenium, Total Cholesterol (TC), triglyceride, High Density Lipoproteins-Cholesterol (HDL-C) by spectrophotometry and Low Density Lipoprotein- Cholesterol (LDL-C) was estimated using Friedewald’s formula. Data were analysed using ANOVA, Chi Square, Student’s t-test and Pearson correlation at p = 0.05. Mean ages for AD (71.1 ±5.0 years), VD (69.0 ±8.2 years) and control (67.5 ±6.8 years) were not significantly different. Mean systolic BP was lower in VD (148.3 ±41.8 mmHg) than AD (156.0 ±36.0 mmHg). Mean BMI, weight and height of the three groups were not significantly different. Mean DHA and EPA in VD (6.7 ±1.9% and 2.4 ±1.7 % of TFA) and AD (5.4 ±2.1% and 3.0 ±1.7% TFA) were lower than in the control (8.9±3.8% and 6.0 ±4.7% TFA) but there were no differences in LA and AA among the three groups. Mean triglyceride and LDL-C were higher in VD (122.7 ±47.3 mg/dL, 101.6 ±28.5 mg/dL) than AD (86.0 ±17.5 mg/dL, 84.7 ±24.6 mg/dL) and control (72.7 ±37.3 mg/dL, 71.2 ±37.1 mg/dL), while UNIVERSITY OF IBADAN LIBRARY iii HDL-C was lower in VD (39.8 ±22.4 mg/dL) than AD (46.2 ±21.3 mg/dL) and control (52.2 ±18.9 mg/dL). Mean homocysteine was higher in VD (9.6 ±1.8 μmol/L) and AD (10.0 ±1.7 μmol/L) than control (6.4 ±3.5 μmol/L). Mean selenium and folate were lower in both VD (1.4 ±0.7 μmol/L, 3.5 ±0.7 ng/mL) and AD (1.5 ±0.6 μmol/L, 5.4 ±0.9 ng/mL) than in control (3.1 ±0.5 μmol/L, 9.5 ±2.8 ng/mL). There were negative correlations between homocysteine and folate (r = -0.67), homocysteine and selenium (r = -0.14) but positive correlations between folate and DHA (r = 0.49); homocysteine and TFA (r = 0.36). Deficiencies of fatty acids, folate and selenium were associated with occurrence of dementia subtypes in Nigerians. Differences in erythrocyte fatty acids levels did not vary distinctly in Vascular dementia and Alzheimer’s disease patients. Omega- 3 fatty and folic acids and antioxidant supplements have the potential to reduce vulnerability to neurodegeneration. Keywords: Senile dementia, polyunsaturated fatty acids, antioxidants.